2017
DOI: 10.15244/pjoes/62905
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Oil-Based Paint from Aqueous Media by Novel Indigenous Brevibacillus parabrevis Strain NAP3 and its Toxicity Assessment

Abstract: The present study sought to explore the bioremediation of oil-based paint from aqueous media using indigenous bacterial isolate Brevibacillus parabrevis strain NAP3 and its toxicity assessment against prokaryotic and eukaryotic biological models. The bacterial isolate was initially screened for bioremediation potential in mineral salts medium containing oil-based paint (conc. 300 ppm, w/v) under shake flask settings. Moreover, the percentage removal of oil-based paint from aqueous media was investigated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…According to Noor et al [5] the knowledge of medicinal plants and their methods of use are confined to aged persons above 50-60 years old. Some of the plants have been tested for their antimicrobial activity and were found to be positive [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…According to Noor et al [5] the knowledge of medicinal plants and their methods of use are confined to aged persons above 50-60 years old. Some of the plants have been tested for their antimicrobial activity and were found to be positive [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Although the method of NP penetration into bacteria is not known absolutely, studies have proposed that the treatment of bacterial culture with NPs causes changes in the membrane morphology of membrane, causing a considerable rise in its permeability, which in turn disturbs suitable transport through the plasma membrane. The bacterial cells have become unable to accurately regulate the transport through the plasma membrane, leading to cell death [31][32][33][34][35][36][37][38][39][40]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The present study showed that each salt medium provided growth conditions for some of the microorganisms found in paint sludge. Micrococcus yunnanensis was isolated from paint sludge in MSM, while in the same medium, Phulpoto et al (27) isolated Brevibacillus parabrevis strains from oil-based paint sludge and Ashwini et al (28) isolated Pseudomonas, Staphylococcus, and Lactobacillus stains. In the direct and serial culture of paint sludge on the NA medium, bacteria, including Rothia amarae, Gor-donia terrae, and Brevibacillus agri were isolated.…”
Section: Discussionmentioning
confidence: 99%